More Is Better : Evaluating the Impact of a Variation in Cash Assistance on the Reintegration Outcomes of Returning Afghan Refugees - Esper, Hisham (World Bank, Washington, DC, 2022)
This paper studies the effect of a change in the amount of cash assistance provided to Afghan refugees returning from Pakistan on household outcomes post-return. Using a regression discontinuity design, it measures the impact of a large exogenous change in cash assistance amounts on post-return outcomes in a quasi-experimental setting. Administrative data and post-return monitoring data suggest that more than 16 months after their return, returnees who received a larger cash allowance of $350 per returnee—equivalent to 2.5 times the average annual pre-return annual income—were better off than those who received a smaller cash allowance of $150. Recipients of the $350 cash assistance were more likely to invest in durable assets, such as a house (17 percentage point difference); recipients of the $150 cash allowance were more likely to use the assistance for immediate food consumption needs (40 percentage point difference). Households that received $350 per returnee were significantly more likely to have been issued legal documentation for their household members. In line with the literature on cash assistance, the change in cash assistance had no effect on post-return employment outcomes. The findings provide new evidence on the effects of unconditional cash transfers on refugee reintegration and show that larger cash transfer programs can have a large and long-term impact following refugees’ return.